Skin - Paolo Di Nardo (And, 2012)
The term SKIN cannot be limited to the two-dimensional aspect of architectural exterior finishing, but must be expanded semantically by making that dimensional leap that leads the 'skin' to assume a three-dimensional role of real space in architecture. A new additional space between the structure or the connective tissue of a building and the external space, assuming in this sense the role of transition between architecture and the city and vice versa: a real semantic space, a space of 'between', a space of passage, the in between of Van Ejck.